2012
DOI: 10.1038/bmt.2012.213
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of adult ALL with central nervous system involvement at diagnosis using autologous and allogeneic transplantation: a study from the Société Française de Greffe de Moelle et de Thérapie Cellulaire

Abstract: To assess the role of hematopoietic SCT (HSCT) in adult ALL patients with central nervous system involvement at diagnosis, we retrospectively analyzed 90 patients who underwent autologous HSCT (auto-HSCT group; n ¼ 27) or allogeneic HSCT (allo-HSCT group; n ¼ 63) and reported to the Socié té Franc¸aise de Greffe de Moelle et de Thé rapie Cellulaire registry between 1994 and 2008. At the time of transplantation, 67 patients (74%) were in first CR, 15 (17%) in CRX2 and 8 (9%) with progressive disease. The 5-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…In our study, as well as in others, 18,49 HSCT represented the most effective therapeutic option with a significant OS benefit compared to patients who relapsed after a previous transplant or who could never undergo a transplant ( p = 0.012). Even if HSCT represents the treatment of choice for VHR patients, in this series it was performed as part of the initial treatment programme only in 18 patients (25.3%) and after a relatively long median time from diagnosis (8 months, range 3–24), despite the fact that 59.2% of the entire cohort was classified as VHR.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In our study, as well as in others, 18,49 HSCT represented the most effective therapeutic option with a significant OS benefit compared to patients who relapsed after a previous transplant or who could never undergo a transplant ( p = 0.012). Even if HSCT represents the treatment of choice for VHR patients, in this series it was performed as part of the initial treatment programme only in 18 patients (25.3%) and after a relatively long median time from diagnosis (8 months, range 3–24), despite the fact that 59.2% of the entire cohort was classified as VHR.…”
Section: Discussionsupporting
confidence: 78%
“…Notably, all six Phlike ALL patients had received previous immunotherapy and one of them had a CNS relapse also after CAR-T-cell therapy, suggesting a neurotropism of this subtype; noteworthy, the combination of ruxolitinib with chemotherapy resulted in a molecular remission in a high-risk Ph-like refractory patient with a macroscopic CSF involvement. 48 In our study, as well as in others, 18,49 HSCT represented the most effective therapeutic option with a significant OS benefit compared to patients who relapsed after a previous transplant or who could never undergo a transplant (p = 0.012). Even if HSCT represents the treatment of choice for VHR patients, in this series it was performed as part of the initial treatment programme only in 18 patients (25.3%) and after a relatively long median time from diagnosis (8 months, range 3-24), despite the fact that 59.2% of the entire cohort was classified as VHR.…”
Section: Discussionsupporting
confidence: 68%
“…The approach to patients with CNS disease and the role for CNS-directed prophylaxis are areas of uncertainty. For patients with CNS disease at diagnosis, a French registry study reported that high-dose TBI and remission status had favorable impacts on OS, regardless of whether the patients underwent auto-HCT or allo-HCT [57]. A single-center analysis showed that patients with a pretransplantation history of CNS involvement were at increased risk for post-transplantation CNS relapse, inferior EFS, and worse OS.…”
Section: Question 7: How To Approach Patients With Central Nervous System (Cns) Disease?mentioning
confidence: 99%
“…6 Moreover, the rate of CNS relapse remained high after allogeneic SCT, including TBI or TBI-free conditioning regimens, in patients with previous CNS involvement. [28][29][30][31] Although the number of patients is limited, this questions allogeneic SCT as being the most efficient way to reduce relapse in patients with CNS disease at diagnosis as it might for patients with other high-risk features such as MRD. 16 The inferior outcome in our patients with initial CNS disease was more likely due to toxicity since higher mortality in remission was observed in patients who received hyper fractionated cyclophosphamide and/or proceeded to allogeneic SCT.…”
Section: Discussionmentioning
confidence: 99%